Sosialisasi Dampak Covid-19 Pada Ekonomi dan Keuangan Keluarga di Lingkungan Rw 01 Kelurahan Cipondoh Indah, Kecamatan Cipondoh, Kota Tangerang - Dewi Murtiningsih; Wendi Usino; Feby Lukito Wibowo (Jurnal Abdimas Adpi Sosial dan Humaniora, 2022)
The development of the corona virus or Covid-19 outbreak in Indonesia is increasing day by day, both positive and dead and those who have recovered are also increasing every day, so the impact of Covid-19 must be a concern, especially for the Sangkuriang village manager and the surrounding community. because the impact of Covid-19 is not only on the economic sector but also on family finances because of the large number of workers who have been laid off or whose working hours have been reduced. The objectives to be achieved from this activity are to help residents to provide understanding and knowledge of Covid-19, to assist the community in adding insight and knowledge regarding the impact of Covid-19 in Kampoeng Sangkuriang, Cipondoh Indah Village, Cipondoh District, Tangerang City. The benefits of community service activities are: Can introduce programs and activities carried out by Budi Luhur University as well as about the existence of this institution to the wider community; It is hoped that it can help the Sangkuriang village manager in Cipondoh Village, Cipondoh District, Tangerang City provide information related to the impact of Covid-19 and can immediately take anticipatory and preventive actions for the community, especially residents of Sangkuriang village; It is hoped that it can provide understanding and insight in understanding the impact of Covid-19 so that the community can apply what is the appeal of the Sangkuriang Village manager.